Promoter methylation of Bax and Bcl2 genes and their expression in patients with Behcet's disease. (8th January 2020) - Asadi, Shahin; Khabbazi, Alireza; Alipour, Shahriar; Abolhasani, Somayeh; Haji, Jafar; Amjadi, Hossein; Sakhinia, Ebrahim
Abstract: BCL2 and BAX genes are a group of signalling inducer and inhibitor genes playing a key role in the process of cellular physiological death (apoptosis). These genes, through the JAK/STAT signalling pathway, affect different cytokines on cell function and subsequently lead to the pathophysiology of diseases, especially autoimmune diseases. In addition, altering the methylation of genes can affect their expression. Since the aetiology and pathology of Behcet's disease is not fully understood, the aim of this study was to determine the methylation pattern of BCL2 and BAX genes in patients with Behcet's disease and compare it with those of control group. This was a case–control study on 51 patients with Behcet and 61 control subjects. Blood samples were received from all subjects. Subsequently, the peripheral blood mononuclear cells (PBMCs) were isolated by Ficoll method and the methylation of the sites was investigated using quantitative methylation specific PCR (qMS‐PCR) technique after extraction of DNA by salting out method and its examination with Nano drop. The results of methylation and expression of Bax gene suggest that the methylation level in the patient group significantly increased compared to the healthy individuals ( p ‐value < .05). Furthermore, the results related to Bax gene expression revealed that the mean of gene expression in the patient group has decreased compared to the healthy group, and this decrease was statistically significant ( p ‐value < .05). The rate of expression and methylation of Bcl2 did not indicate any change in the two patient and healthy groups. Given the results of this study, it can be guessed that perhaps DNA methylation is involved in certain conditions of the disease and it may result in regulation of the expression of the involved genes such as Bax gene, in the pathogenesis of the disease.